2017
DOI: 10.1186/s12864-017-4287-0
|View full text |Cite
|
Sign up to set email alerts
|

Independent impacts of aging on mitochondrial DNA quantity and quality in humans

Abstract: BackgroundThe accumulation of mitochondrial DNA (mtDNA) mutations, and the reduction of mtDNA copy number, both disrupt mitochondrial energetics, and may contribute to aging and age-associated phenotypes. However, there are few genetic and epidemiological studies on the spectra of blood mtDNA heteroplasmies, and the distribution of mtDNA copy numbers in different age groups and their impact on age-related phenotypes. In this work, we used whole-genome sequencing data of isolated peripheral blood mononuclear ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
94
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 82 publications
13
94
1
Order By: Relevance
“…180 (99%) lymphoblasts possessed at least one heteroplasmy in mtDNA ( Figure S3B). Similar to our previous study on lymphoblast mtDNA (5), the number of mtDNA heteroplasmies identified in lymphoblasts was consistently greater than those of whole blood, at about 1 heteroplasmy of VAF≥1-2% (14,16), implying that mtDNA of lymphoblasts may enrich for pre-existing variants in somatic cells that are undetectable at a tissue level.…”
Section: Age-dependent Increase Of Heteroplasmy Incidence In Lymphoblsupporting
confidence: 87%
See 3 more Smart Citations
“…180 (99%) lymphoblasts possessed at least one heteroplasmy in mtDNA ( Figure S3B). Similar to our previous study on lymphoblast mtDNA (5), the number of mtDNA heteroplasmies identified in lymphoblasts was consistently greater than those of whole blood, at about 1 heteroplasmy of VAF≥1-2% (14,16), implying that mtDNA of lymphoblasts may enrich for pre-existing variants in somatic cells that are undetectable at a tissue level.…”
Section: Age-dependent Increase Of Heteroplasmy Incidence In Lymphoblsupporting
confidence: 87%
“…But only mtDNA heteroplasmy incidence showed a significant difference between these two age groups ( Figure 4G; Cohen's d=0.42, P=0.0055). The lack of a significant association of mtDNA content with age ( Figure 4H; Cohen's d=-0.12, P=0.44 for STAMP-CN; Cohen's d=-0.07, P=0.71 for qPCR-CN) might be due to insufficient statistical power, since only a mild annual decrease of 0.4 mtDNA copies (0.24% of the population average in 1511 individuals, P=0.0097) in blood was noted in our previous study (14).…”
Section: Age-dependent Increase Of Heteroplasmy Incidence In Lymphoblmentioning
confidence: 64%
See 2 more Smart Citations
“…Studies that use multiple mitochondrial biomarkers have revealed only a slight intercorrelation between the markers and aging, suggesting that they tap into different biological dimensions (Lara et al, 2015;Larsen et al, 2012;Marrocco, Altieri, & Peluso, 2017;Xia, Chen, McDermott, & Han, 2017). Recent data support the hypothesis that mtDNA copy number and degree of heteroplasmy-assessed in human blood cells and in tissue biopsies-provide information on mitochondrial physiology that is relevant for aging and age-related diseases (McDermott et al, 2018;Moore et al, 2017;Zhang, Wang, Ye, Picard, & Gu, 2017). Both measurements can be utilized via PCR methods or, more recently, by derivation from genome sequencing data (Ding et al, 2015).…”
Section: Mitochondrial Functionmentioning
confidence: 86%